The Neumann Bands in Ferrite (175542e1-2188-434f-817e-0067f35126d0) - C. H. Mathewson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1928)
ABOUT fifty pages of Henry M. Howe's profound treatise, "The Metallography of Steel and Cast Iron," are devoted to twinning with special reference to the origin, nature and general significance of the Neumann bands in ferrite. Howe believed with Osmond and Cartaud1 that the Neumanns are mechanical twins and his careful observations leave no doubt that these straight-sided narrow bands habitually occur parallel to trapezohedral planes of form {211}. Attempt's to develop the structure of the bands by various methods so that their identity could be established beyond question have not been conspicuously successful. Howe thought that they deflected slip bands. Some of the etching figures which have been developed within and adjacent to Neumann bands support the contention that they are twins. A good example of this effect in ferrite containing 0.6 per cent. of nickel and 1.3 per cent. of phosphorus, originally due to Harnecker and Rassow,2 was reproduced in. the 1928 lecture before the Institute of Metals Division on twinning in metals.3 In this case, the sides of the figures might represent the traces of cubic planes laid bare by etching a properly oriented grain of ferrite, twinned along a plane of form {211}. Our own observations in this direction may be represented by Fig. 1 which shows in a deeply etched cavity in the boundary region between a Neumann band and the original crystal two small crystal surfaces which resemble the faces meeting at a reentrant angle in the simple cube twinned along a bisecting plane of form {211} as sketched in Fig. 2.